Hubungan Antara Fear of Missing Out (FoMo) dan Social Media Fatigue (SMF) Pada Mahasiswa - Andariska Nurissam, Sofie; Yogi Wulandari, Primatia (Jurnal Syntax Fusion, 2023)
As a student, of course, you have main tasks that need to be done, but along with the increasing sophistication of technology, social media has emerged which makes students divert their activities to social media. Active involvement in social media will encourage individuals to continue to be connected with social media, further causing Fear of missing Out (FoMo). The existence of intense involvement with social media can have an impact in the form of excess information, because when individuals feel FoMo, they will tend to use social media in all ways, so that it can cause individuals to experience Social media fatigue (SMF). This study aims to determine whether there is a relationship between fear of missing out (FoMo) and Social media fatigue (SMF) in college students. This research is a quantitativeresearch with survey method. The number of respondents was 108 consisting of men and women aged 18-25 years. The measuring tool used is FoMo which was compiled by Przybylski et al. (2013) and the SMF compiled by Zhang et al. (2021) which is then translated. The results of the data analysis show that there is a relationship between FoMo and SMF in college students. The two variables have a positive correlation. In this case, it is concluded that the higher the FoMo, the higher the SMF experienced by students